Association of Child Maltreatment and Deployment-related Traumatic Experiences with Mental Disorders in Active Duty Service Members and Veterans of the Canadian Armed Forces: Association de la Maltraitance des Enfants et des Expériences Traumatisantes Liées au Déploiement Avec les Troubles Mentaux Chez les Membres du Service Actif et Les Anciens Combattants des Forces Armées Canadiennes. (November 2021) - Afifi, Tracie O.; Sareen, Jitender; Taillieu, Tamara; Stewart-Tufescu, Ashley; Mota, Natalie; Bolton, Shay-Lee; Asmundson, Gordon J. G.; Enns, Murray W.; Ports, Katie A.; Jetly, Rakesh
Objective: Mental health among military personnel is an important public health priority. It is known that military personnel experience a high prevalence of child maltreatment and deployment-related traumatic events (DRTEs) and both are related to mental health outcomes. However, few, if any, studies have examined the cumulative and interactive effects of child maltreatment and DRTEs on mental health disorders in a sample of active duty service members and military veterans. Methods: Data were from the Canadian Armed Forces (CAF) Members and Veterans Mental Health Follow-up Survey collected in 2018 ( N = 2, 941, response rate = 68.7%), a 16-year follow-up survey of CAF Regular Force members interviewed in 2002. Five types of child maltreatment and 10 types of DTREs were assessed for impact on mental health. Mental disorders included past 12-month generalized anxiety disorder (GAD), panic disorder, social phobia, and major depressive episode (MDE). Past 12-month symptoms of posttraumatic stress disorder (PTSD) were also examined. Results: The prevalence of any exposure to child maltreatment and DRTEs was 62.5% and 68.6%, respectively. All types of child maltreatment were associated with increased odds of past 12-month PTSD symptoms and mental disorders with the exception of physical abuse and GAD as well as childhood exposure to intimate partner violence and panic disorder. Cumulative effects of having experienced both child maltreatment and DRTEs increased the odds of past 12-month PTSD symptoms, GAD, social phobia, and MDE. No interaction effects were significant. Conclusions: The prevalence of a child maltreatment history is high among active Canadian military and veterans. As well, child maltreatment may increase the likelihood of mental disorders across the life span. This may be especially true for individuals who also experience DRTEs. Understanding these relationships may provide insight into developing effective interventions for military personnel and veteran mental health outcomes.